Resistance to RHD virus in wild Australian rabbits: Comparison of susceptible and resistant individuals using a genomewide approach - Nina I. Schwensow; Harald Detering; Stephen Pederson; Camila Mazzoni; Ron Sinclair; David Peacock; John Kovaliski; Brian Cooke; Jörns Fickel; Simone Sommer (Molecular Ecology, 2017)
Deciphering the genes involved in disease resistance is essential if we are to understand host–pathogen coevolutionary processes. The rabbit haemorrhagic disease virus ( RHDV ) was imported into Australia in 1995 as a biocontrol agent to manage one of the most successful and devastating invasive species, the European rabbit ( Oryctolagus cuniculus ). During the first outbreaks of the disease, RHDV caused mortality rates of up to 97%. Recently, however, increased genetic resistance to RHDV has been reported. Here, we have aimed to identify genomic differences between rabbits that survived a natural infection with RHDV and those that died in the field using a genomewide next‐generation sequencing ( NGS ) approach. We detected 72 SNP s corresponding to 133 genes associated with survival of a RHD infection. Most of the identified genes have known functions in virus infections and replication, immune responses or apoptosis, or have previously been found to be regulated during RHD . Some of the genes identified in experimental studies, however, did not seem to play a role under natural selection regimes, highlighting the importance of field studies to complement the genomic background of wildlife diseases. Our study provides a set of candidate markers as a tool for the future scanning of wild rabbits for their resistance to RHDV . This is important both for wild rabbit populations in southern Europe where RHD is regarded as a serious problem decimating the prey of endangered predator species and for assessing the success of currently planned RHDV variant biocontrol releases in Australia.

High adaptive variability and virus-driven selection on major histocompatibility complex (MHC) genes in invasive wild rabbits in Australia - Nina Schwensow; Camila J. Mazzoni; Elena Marmesat; Joerns Fickel; David Peacock; John Kovaliski; Ron Sinclair; Phillip Cassey; Brian Cooke; Simone Sommer (Biological Invasions, 2017)

Molecular epidemiology of R abbit H aemorrhagic D isease V irus in A ustralia: when one became many - John Kovaliski; Ron Sinclair; Greg Mutze; David Peacock; Tanja Strive; Joana Abrantes; Pedro J. Esteves; Edward C. Holmes (Molecular Ecology, 2014)
R abbit H aemorrhagic D isease V irus ( RHDV ) was introduced into A ustralia in 1995 as a biological control agent against the wild E uropean rabbit ( O ryctolagus cuniculus ). We evaluated its evolution over a 16‐year period (1995–2011) by examining 50 isolates collected throughout A ustralia, as well as the original inoculum strains. Phylogenetic analysis of capsid protein VP 60 sequences of the A ustralian isolates, compared with those sampled globally, revealed that they form a monophyletic group with the inoculum strains ( CAPM V‐351 and RHDV 351 INOC ). Strikingly, despite more than 3000 rereleases of RHDV 351 INOC since 1995, only a single viral lineage has sustained its transmission in the long‐term, indicative of a major competitive advantage. In addition, we find evidence for widespread viral gene flow, in which multiple lineages entered individual geographic locations, resulting in a marked turnover of viral lineages with time, as well as a continual increase in viral genetic diversity. The rate of RHDV evolution recorded in A ustralia −4.0 (3.3–4.7) × 10 −3 nucleotide substitutions per site per year – was higher than previously observed in RHDV , and evidence for adaptive evolution was obtained at two VP 60 residues. Finally, more intensive study of a single rabbit population (Turretfield) in S outh A ustralia provided no evidence for viral persistence between outbreaks, with genetic diversity instead generated by continual strain importation.

Rabbit Haemorrhagic Disease: Applying Occam’s Razor to competing hypotheses - DAVID PEACOCK; GREG MUTZE; RON SINCLAIR; JOHN KOVALISKI; BRIAN COOKE (Molecular Ecology, 2012)
Rabbit haemorrhagic disease virus (RHDV) is a highly virulent lagovirus endemic in Europe and Australasian populations of the European rabbit, Oryctolagus cuniculus . It has also caused several unexplained disease outbreaks in domestic European rabbits in North America. Non‐pathogenic spread of RHDV leading to persistent infection which later reactivated has recently been proposed as the cause of overt disease and death of a pet rabbit in Canada, the first confirmed case of Rabbit haemorrhagic disease in that country. We suggest that there is little evidence to support non‐pathogenic spread of virulent RHDV, some evidence that is contradictory, and evidence to support a simpler alternative hypothesis. RHDV can be spread over long distances between sparse rabbit populations by fomites or flying insects. Although highly pathogenic, RHDV can be limited in its spread within rabbit populations, or its presence masked by closely related but non‐pathogenic lagoviruses which can provide protection against acute disease. In the absence of any evidence from clinical studies to support reactivation of persistent RHDV infection, the simpler explanation seems more likely to be correct.

Baseline Ecological Risk Assessment of the Calcasieu Estuary, Louisiana: Part 2. An Evaluation of the Predictive Ability of Effects-Based Sediment-Quality Guidelines - Donald D. MacDonald; Christopher G. Ingersoll; Dawn E. Smorong; Jesse A. Sinclair; Rebekka Lindskoog; Ning Wang; Corrine Severn; Ron Gouguet; John Meyer; Jay Field (Archives of Environmental Contamination and Toxicology, 2011)

Baseline Ecological Risk Assessment of the Calcasieu Estuary, Louisiana: Part 3. An Evaluation of the Risks to Benthic Invertebrates Associated With Exposure to Contaminated Sediments - Donald D. MacDonald; Christopher G. Ingersoll; Nile E. Kemble; Dawn E. Smorong; Jesse A. Sinclair; Rebekka Lindskoog; Gary Gaston; Denise Sanger; R. Scott Carr; James Biedenbach; Ron Gouguet; John Kern; et al. (Archives of Environmental Contamination and Toxicology, 2011)

Invasive species can't cover their tracks: using microsatellites to assist management of starling ( Sturnus vulgaris ) populations in Western Australia - LEE ANN ROLLINS; ANDREW P. WOOLNOUGH; ALAN N. WILTON; RON SINCLAIR; WILLIAM B. SHERWIN (Molecular Ecology, 2009)
Invasive species are known to cause environmental and economic damage, requiring management by control agencies worldwide. These species often become well established in new environments long before their detection, resulting in a lack of knowledge regarding their history and dynamics. When new invasions are discovered, information regarding the source and pathway of the invasion, and the degree of connectivity with other populations can greatly benefit management strategies. Here we use invasive common starling ( Sturnus vulgaris ) populations from Australia to demonstrate that genetic techniques can provide this information to aid management, even when applied to highly vagile species over continental scales. Analysis of data from 11 microsatellites in 662 individuals sampled at 17 localities across their introduced range in Australia revealed four populations. One population consisted of all sampling sites from the expansion front in Western Australia, where control efforts are focused. Despite evidence of genetic exchange over both contemporary and historical timescales, gene flow is low between this population and all three more easterly populations. This suggests that localized control of starlings on the expansion front may be an achievable goal and the long‐standing practice of targeting select proximal eastern source populations may be ineffective on its own. However, even with low levels of gene flow, successful control of starlings on the expansion front will require vigilance, and genetic monitoring of this population can provide essential information to managers. The techniques used here are broadly applicable to invasive populations worldwide.